Radiofrequency irradiation attenuates angiogenesis and inflammation in UVB‐induced rosacea in mouse skin. Issue 7 (9th July 2020) - Son, Myeongjoo; Park, Joonhong; Oh, Seyeon; Choi, Junwon; Shim, Minjung; Kang, Donghwan; Byun, Kyunghee
Abstract: Rosacea is a skin inflammatory condition accompanied by cutaneous signs such as oedema, flushing, erythema, telangiectasia and pustules. Generally, rosacea is triggered by ultraviolet B (UVB) exposure. When exposed to UVB, skin epidermis thickens and produces elevated levels of pro‐inflammatory cytokines, especially keratinocyte‐related VEGF, a potent angiogenic factor. The upregulations of VEGF expression and its secretion promote the formation of new blood vessels and exacerbates rosacea. In this study, radiofrequency (RF) irradiation reduced keratinocyte proliferation in the epidermal layer, the expressions of pro‐inflammatory cytokines, angiogenesis‐related inflammatory factors and VEGF in our UVB‐induced model of rosacea in vitro and in vivo. RF irradiation attenuated VEGF‐induced angiogenesis‐associated processes such as tube formation, cell migration and endothelial cell proliferation. Notably, blood vessel densities in the skins of UVB‐treated mice and rosacea patients were significantly decreased by RF irradiation. These results provide experimental and molecular evidence regarding the effectiveness of RF irradiation for the treatment of rosacea.